The role of the Polish financial supervision authority in the new European architecture of supervision over the financial market - Fedorowicz, Magdalena; Zalcewicz, Anna (University of Wroclaw. Faculty of Law, Administration & Economics, 2012)
The purpose of this paper is to analyze the main provisions of the regulation of European financial supervision from the perspective of the competencies and functions of the Polish Financial Supervision Authority (KNF). It was also considered necessary by the Authors to present the current tasks, aims and competencies of the KNF.The implementation of a new supervisory structure in the EU brought about changes to the functioning of the KNF. These changes are particularly visible in the regulatory functions as domestic supervisory authorities are obliged to introduce uniform supervisory standards defined on a European level. The current reform of the European financial markets has shown that the role of national supervisors in the financial safety net requires a new approach. It is obvious that in these times of financial crisis, national supervisors must incur significant costs, namely the functional reduction of regulatory independence in some matters.This paper is a contribution to the discussion on the course of the development of Polish and EU financial markets supervision.
Keywords: nadzór finansowy; rynek finansowy Unii Europejskiej; Polska